2018
DOI: 10.1021/acs.jpcb.8b06704
|View full text |Cite
|
Sign up to set email alerts
|

Global Small-Angle X-ray Scattering Data Analysis of Triacylglycerols in the Molten State (Part I)

Abstract: The study of triacylglycerols (TAGs) in their molten state is of fundamental importance for a deeper understanding of the TAG crystallization processes, being highly relevant for both manufacturing and medical applications. Although different models have been proposed to explain the nanostructured nature of the fluid state of TAGs, none of them are fully satisfactory. In this paper, we propose a new model consisting of positionally uncorrelated lamellar TAG assemblies embedded in an isotropic medium that assis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 100 publications
2
16
0
Order By: Relevance
“…More specifically, from our NMRD analysis (Figure ), we consider that the increase of R 1 at very low frequencies is related to ODFs, similarly to what has been observed previously in nematic and smectic phases . These ODFs could be explained in the light of our newly proposed model of the structured clusters of molten TAGs . Briefly, TAGs are thought to assemble in clusters immersed in an isotropic medium of TAGs from which some molecules start interacting with the outer fatty acids, thus creating an additional layer, or shell, which increases in coverage as temperature decreases.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…More specifically, from our NMRD analysis (Figure ), we consider that the increase of R 1 at very low frequencies is related to ODFs, similarly to what has been observed previously in nematic and smectic phases . These ODFs could be explained in the light of our newly proposed model of the structured clusters of molten TAGs . Briefly, TAGs are thought to assemble in clusters immersed in an isotropic medium of TAGs from which some molecules start interacting with the outer fatty acids, thus creating an additional layer, or shell, which increases in coverage as temperature decreases.…”
Section: Discussionsupporting
confidence: 79%
“…[22,43,44] These ODFs could be explained in the light of our newly proposed model of the structured clusters of molten TAGs. [33,37] Briefly, TAGs are thought to assemble in clusters immersed in an isotropic medium of TAGs from which some molecules start interacting with the outer fatty acids, thus creating an additional layer, or shell, which increases in coverage as temperature decreases. These clusters might begin to orientate once a crystallisation-inducing temperature (such as 22°C) is reached, generating some of the first lamellar structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those papers addressed questions regarding the role played by polymer selfand mutual-entanglement in the kinetics of memory effects.Recently, TAG crystallization has been studied [15][16][17][18]. Coexistence of solid and liquid state TAGs were reported [16]. The second paper [11] is especially interesting because it showed that the power law behavior of the overall crystal growth rate, found previously to be different for melts with and without memory, and interpreted in terms of changes in the structure and/or the dynamics of the entangled melt states, was not found in their NMR results.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon has been studied for linear polymers [10][11][12], as well as for cocoa butter [13] and fatty acids [14]. Those papers addressed questions regarding the role played by polymer selfand mutual-entanglement in the kinetics of memory effects.Recently, TAG crystallization has been studied [15][16][17][18]. Coexistence of solid and liquid state TAGs were reported [16].…”
Section: Introductionmentioning
confidence: 99%